Arbil, Irak. Ausgrabungen und Survey im Stadtgebiet von Arbil. Die Arbeiten des Jahres 2016 - Hausleiter, Arnulf; van Ess, Margarete (e-Forschungsberichte des DAI, 2017)
In the context of a study season, the diagnostic pottery from the post-Assyrian occupation above the Neo-Assyrian tomb excavated in the city of Arbil between 2009 and 2011 as well as the surface ceramics collected during the 2015 lower town survey was completely processed. Whereas the material from the excavations was dominated by Iron Age specimens, the composition of the survey material is markedly different. More than half of the ceramics has been identified as belonging to the early to middle Islamic periods – meaningful expression of the significance of Arbil in the post-classical periods. In Germany, based on a rectified Pleiades satellite image of 2013, a 3D-model of the lower town area of Arbil was generated, indicating ancient topographic features suggesting a reconstruction of the perimeter wall ofthe lower town different from previous hypotheses.